New Mastoparan Peptides in the Venom of the Solitary Eumenine Wasp Eumenes micado - Konno, Katsuhiro (Toxins (Basel), 2019)
Comprehensive LC-MS and MS/MS analysis of the crude venom extract from the solitary eumenine wasp Eumenes micado revealed the component profile of this venom mostly consisted of small peptides. The major peptide components, eumenine mastoparan-EM1 (EMP-EM1: LKLMGIVKKVLGAL-NH(2)) and eumenine mastoparan-EM2 (EMP-EM2: LKLLGIVKKVLGAI-NH(2)), were purified and characterized by the conventional method. The sequences of these new peptides are homologous to mastoparans, the mast cell degranulating peptides from social wasp venoms; they are 14 amino acid residues in length, rich in hydrophobic and basic amino acids, and C-terminal amidated. Accordingly, these new peptides can belong to mastoparan peptides (in other words, linear cationic α-helical peptides). Indeed, the CD spectra of these new peptides showed predominantly α-helix conformation in TFE and SDS. In biological evaluation, both peptides exhibited potent antibacterial activity, moderate degranulation activity from rat peritoneal mast cells, and significant leishmanicidal activity, while they showed virtually no hemolytic activity on human or mouse erythrocytes. These results indicated that EMP-EM peptides rather strongly associated with bacterial cell membranes rather than mammalian cell membranes.